Novel compound heterozygous variants in the CSPP1 gene causes Joubert syndrome: case report and literature review of the CSPP1 gene’s pathogenic mechanism - Wei, Caichuan; Zhang, Haiju; Fu, Miaoying; Ye, Jingping; Yao, Baozhen (Frontiers in Pediatrics, 2024)
Joubert syndrome (JS) is a rare autosomal recessive neurodevelopmental condition characterized by congenital mid-hindbrain abnormalities and a variety of clinical manifestations. This article describes a case of Joubert syndrome type 21 with microcephaly, seizures, developmental delay and language regression, caused by a CSPP1 gene variant and examines the contributing variables. This paper advances the understanding of JS by summarizing the literature and offering detection patterns for practitioners with clinical suspicions of JS.